Social Dynamics in Public Administration: A Case Study of Local Government - A. Octamaya Tenri Awaru (Program Pascasarjana Universitas Negeri Makassar, 2024)
This study explores the social dynamics within public administration through a case study of local government in Indonesia. The research aims to understand how social interactions, relationships, and structures influence the effectiveness and efficiency of public administration at the local level. Utilizing a qualitative approach, data were collected through interviews, observations, and document analysis. The findings reveal that social dynamics, including community engagement, leadership styles, and inter-departmental cooperation, significantly impact policy implementation and public service delivery. Additionally, the study highlights the importance of social capital in fostering collaboration and trust among stakeholders. The implications of these findings suggest that local governments should prioritize social dynamics in their administrative processes to enhance governance outcomes. This research contributes to the broader discourse on the interplay between sociology and public administration, offering insights for policymakers and practitioners in Indonesia and beyond.